The Influence of Spiritual Leadership, Servant Leadership, and Organizational Citizenship Behavior on Employee Performance PT Varia Usaha Beton - Mahatmaja, Arfan; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the effect of Spiritual Leadership, Servant Leadership, and Organizational Citizenship Behavior on Employee Performance. PT Varia Usaha Beton. The research was conducted using a quantitative approach and data collection was done through a questionnaire. The sample in this study was 99 permanent employees of PT Varia Usaha Beton. The data obtained were analyzed using Smart PLS Version 4.0 software. The results of this study are that Servant Leadership has a significant effect on Organizational Citizenship Behavior (OCB), Servant Leadership has a significant effect on Employee Performance, and Organizational Citizenship Behavior has a positive and significant effect on Employee Performance at PT Varia Usaha Beton.